2011
DOI: 10.1007/s12185-010-0748-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the terminal complement inhibitor eculizumab in Japanese patients with paroxysmal nocturnal hemoglobinuria: the AEGIS Clinical Trial

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a progressive and life-threatening disease characterized by complement-mediated chronic hemolysis, resulting in serious life-threatening complications and early mortality. Eculizumab, a humanized anti-C5 monoclonal antibody that inhibits terminal complement activation, has been shown to reduce hemolysis in PNH patients. The pivotal open-label, 12-week phase II registration study (AEGIS) was designed to evaluate the efficacy and safety of eculizumab in Japanese patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…Of note, the racial differences disappeared when assembling PNH patients with a total leukocyte count ≥3.0x10 8 /l among patients showing evident hemolysis with more than 50% PNH granulocytes ( Figure 1D). Taken together, although hemolysis contributes to the incidence of PNH thrombosis (data not shown), which supports the allegedly identical amelioration of PNH thrombosis after the administration of eculizumab [1,3], it is no longer regarded as a major cause of racial differences ( Figure 1C). Of interest, racial differences were detected among patients with a total leukocyte count <3.0x10 8 /l containing more than 50% PNH clones ( Figure 1D), which implies that underlying factors such as genetic conditions are involved in conventional thrombus formation, even in PNH patients, because these factors make PNH thrombosis likely to be less affected by a possible specific feature of PNH granulocytes and hemolysis.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Of note, the racial differences disappeared when assembling PNH patients with a total leukocyte count ≥3.0x10 8 /l among patients showing evident hemolysis with more than 50% PNH granulocytes ( Figure 1D). Taken together, although hemolysis contributes to the incidence of PNH thrombosis (data not shown), which supports the allegedly identical amelioration of PNH thrombosis after the administration of eculizumab [1,3], it is no longer regarded as a major cause of racial differences ( Figure 1C). Of interest, racial differences were detected among patients with a total leukocyte count <3.0x10 8 /l containing more than 50% PNH clones ( Figure 1D), which implies that underlying factors such as genetic conditions are involved in conventional thrombus formation, even in PNH patients, because these factors make PNH thrombosis likely to be less affected by a possible specific feature of PNH granulocytes and hemolysis.…”
supporting
confidence: 52%
“…Eculizumab, an inhibitor of terminal complement C5, provides patients with PNH with a good quality of life by ameliorating hemolysis and thrombosis, and promotes a better understanding of the complement-mediated molecular pathophysiology of PNH [1][2][3]. However, the underlying reasons for distinct differences in the incidences of thrombosis and bone marrow failure between Caucasian and Asian patients with PNH are still unknown (West vs. Japan, 32% vs. 4%) [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Eculizumab effectively controls intravascular hemolysis and its direct consequences in PNH patients, which results in remarkable clinical improvement. 1,3 The natural history of the disease, which had already improved before the introduction of eculizumab (compare the data reported by Hillmen et al, 1995 4 with those reported by de Latour et al, 2008 5 ), may have improved further with the use of this agent. 6 However, the hematologic response to eculizumab is variable.…”
Section: Introductionmentioning
confidence: 87%
“…However, HSCT is known to produce high complication rates, mortality, and is performed only for certain indications in cases of hematopoietic aplasia [4,13].…”
Section: Introductionmentioning
confidence: 99%